Additional synthesis on thiophene-containing trisubstituted methanes (TRSMs) as inhibitors of M. tuberculosis and 3D-QSAR studies. Issue 11 (1st November 2016) - Singh, P.; Saha, T.; Mishra, P.; Parai, M. K.; Ireddy, S.; Lavanya Kumar M., S.; Krishna, S.; Kumar, S. K.; Chaturvedi, V.; Sinha, S.; Siddiqi, M. I.; Panda, G.
Abstract: We earlier reported thiophene-containing trisubstituted methanes (TRSMs) as novel cores carrying anti-tubercular activity, and identified S006-830 as the phenotypic lead with potent bactericidal activity against single- and multi-drug resistant clinical isolates of Mycobacterium tuberculosis ( M. tb ). In this work, we carried out additional synthesis of several TRSMs. The reaction scheme essentially followed the Grignard reaction and Friedel–Crafts alkylation, followed by insertion of a dialkylaminoethyl chain. We also performed microbiological evaluations including in vitro screening against the virulent strain M. tb H37Rv, cytotoxicity assessment in the Vero C-1008 cell line, and 3D-QSAR studies with comparative molecular field analysis (CoMFA) and comparative molecular similarity index analysis (CoMSIA). CoMFA and CoMSIA models yielded good statistical results in terms of q 2 and r 2 values, suggesting the validity of the models. It was concluded that a para-substituted benzene ring with bulkier electron-donating groups and aminoalkyl chains are required for higher inhibitory capacity against M. tuberculosis . We believe that these insights will rationally guide the design of newer, optimal, TRSMs.